Learning analytics support to teachers' design and orchestrating tasks - Amarasinghe, Ishari; Michos, Konstantinos; Crespi, Francisco; Hernández‐Leo, Davinia (Journal of computer assisted learning, 2024)
Background Data‐driven educational technology solutions have the potential to support teachers in different tasks, such as the designing and orchestration of collaborative learning activities. When designing, such solutions can improve teacher understanding of how learning designs impact student learning and behaviour; and guide them to refine and redesign future learning designs. When orchestrating educational scenarios, data‐driven solutions can support teacher awareness of learner participation and progress and enhance real time classroom management. Objectives The use of learning analytics (LA) can be considered a suitable approach to tackle both problems. However, it is unclear if the same LA indicators are able to satisfactorily support both the designing and orchestration of activities. This study aims to investigate the use of the same LA indicators for supporting multiple teacher tasks, that is, design, redesign and orchestration, as a gap in the existing literature that requires further exploration. Methods In this study, first we refer to the previous work to study the use of different LA to support both tasks. Then we analyse the nature of the two tasks focusing on a case study that uses the same collaborative learning tool with LA to support both tasks. Implications The study findings led to derive design considerations on LA support for teachers’ design and orchestrating tasks. Lay Description What is already known about this topic The alignment of Learning Analytics (LA) with Learning Design provides opportunities for teachers to inquire into student learning and to support pedagogical design decision making. Access to LA during the run‐time of learning situations has the potential to augment teachers' actionability and interventions during their orchestration. It is not clear whether the same LA indicators would be able to support both learning design and orchestration and whether commonalities or differences exist in analytics use. What this paper adds A critical and thoughtful assessment of the related literature to indicate the use of different LA indicators to support design and orchestration tasks. Details of two cases in which teachers used different LA indicators to guide their design and orchestration of Pyramid pattern based scripted collaborative learning scenarios. An exploration and an analysis of the similarities and the differences of the use of LA indicators for two teacher tasks, that is, design and orchestration. Implications for practice and/or policy Data‐driven insights from LA benefits teachers during design and orchestration. Same LA indicators serve different purposes during design and orchestration. Teachers may easily get overloaded with high amount of LA indicators, further research is required to explore the related aspects.